Endogenous Timing and the Taxation of Discrete Investment Choices - Paolo Panteghini (Center for Economic Studies and ifo Institute (CESifo), 2002)
This article discusses the effects of taxation on the discrete choice of alternative projects. In particular, it is shown that if taxation affects the optimal timing of irreversible investment, then the discrete choice is distorted as well. This result has both methodological and political implications.
Keywords: H25; H32; 330; effective average tax rate; timing and real options